Respuesta :

Answer:

H is the Answer

Step-by-step explanation:

Apply distance formula.

[tex](x {}^{2 } - {x}^{1} ) {}^{2} + ( {y}^{2} - {y}^{1} ) {}^{2} = d {}^{2} [/tex]

where d is the distance.

[tex]( - 5 - 7) {}^{2} + (0 - 5) {}^{2} = [/tex]

[tex] - 12 {}^{2} + - 5 {}^{2} = {d}^{2} [/tex]

[tex] \sqrt{169} = {d}^{2} [/tex]

[tex]d = 13[/tex]

Answer:

H, 13

Step-by-step explanation:

Distance formula:

[tex]\sqrt{(x_2-x_1)^2+(y_2-y_1)^2} \\\sqrt{(7-(-5))^2+(-5-0)^2}\\\sqrt{144+25}\\\sqrt{169}\\13[/tex]